Effects of loneliness， social support and social media use on post-traumatic stress symptoms among post-earthquake adolescents - Guo Zhaoran; Che Qicheng; Wu Zhihong; Shi Wei (Sichuan jingshen weisheng)
BackgroundPost-traumatic stress symptoms （PTSS） is highly prevalent in adolescents who have experienced earthquake， which seriously threatens their physical and mental health， yet there is currently a lack of research on the effects of loneliness， social support and social media use on PTSS among post-earthquake adolescents.ObjectiveTo assess the PTSS among adolescents experiencing MS6.0 Luxian， Sichuan， earthquake on 16 September 2021， and to investigate the effects of loneliness， social support and social media use on PTSS， so as to provide references for the intervention of PTSS among post-earthquake adolescents.MethodsOn November 12， 2021， simple random sampling technique was used to select 2 522 post-earthquake adolescents in Luxian county of Luzhou city in Sichuan province. All subjects were assessed using Post-Traumatic Stress Disorder Checklist for DSM-5 （PCL-5）， Multidimensional Scale of Perceived Social Support （MSPSS）， Short-form UCLA Loneliness Scale （ULS-3） and Social Media Use Scale （SM-10）. Binary Logistic regression was used to determine the factors influencing PTSS among post-earthquake adolescents.ResultsPTSS was detected in 91 （3.61%） adolescents. Binary Logistic regression revealed that perceived social support from family members （OR=0.926， 95% CI： 0.879~0.976） was a protective factor for PTSS among post-earthquake adolescents. Lack of companionship （OR=1.764， 95% CI： 1.141~2.727）， feeling isolated （OR=2.037， 95% CI： 1.282~3.236）， and viewing negative emotional response of disaster victims through social media （OR=1.615， 95% CI： 1.291~2.020） were risk factors for PTSS among post-earthquake adolescents.ConclusionLack of companionship， feeling isolated， and viewing negative emotional response of disaster victims through social media pose a negative impact on PTSS among post-earthquake adolescents， while perceived social support from family members exert a positive impact on PTSS among post-earthquake adolescents. ［Funded by Humanity and Social Science Youth foundation of Ministry of Education of China （number， 22YJC190019）； Natural Science Foundation of Sichuan Province （number， 2023NSFSC1486）］